PARP Inhibitors in First-Line Therapy of Ovarian Cancer: Are There Any Doubts? - Franzese, Elisena; Diana, Anna; Centonze, Sara; Pignata, Sandro; De Vita, Ferdinando; Ciardiello, Fortunato; Orditura, Michele (Frontiers in Oncology, 2020)
The standard of care for newly diagnosed advanced ovarian cancer (NADOC) is represented by surgical de-bulking followed by systemic platinum–taxanes combination chemotherapy. At last ESMO congress results from three trials testing three different PARP inhibitors (olaparib, niraparib, veliparib) in first line therapy of OC have been presented. For the first time, these studies evaluated the efficacy of PARP-inhibitors in this setting and the relative predictive biomarkers for patients’ selection. The use of a PARP inhibitor is related with prolonged PFS in the whole population of NADOC, although the magnitude of benefit varies widely among subgroups, highlighting the need to identify specific biological subtypes into clinical practice. In this mini-review we discuss the updated data available from clinical studies in this scenario.